The Rohingya crisis: An analysis of international response, 2016-2017 - Hossain, Ishtiaq (2017)
Throughout 2017, the situation in Myanmar’s northern Rakhine State has deteriorated significantly with potential long-term consequences for regional security and stability. So states a report by the London-based Institute for International and Strategic Studies. This paper examines the international response to the Rohingya crisis.